Navigating the Bangladeshi Market: Unlocking Market Entry Opportunities for STARBUCKS - Quadir, Proma; Ansar, Tazrian Binte; Dembo, Sardauna AbdulSobur; Zaheen, Tasfia; Raisa, Khadiza Afroz (Business Perspective Review, 2024)
Purpose: This study aims to analyze Starbucks' potential entry into the Bangladeshi market, considering its potential for growth and alignment with the company's business model. It evaluates market characteristics and examines Starbucks' strategies for suitability. Method: The study utilizes market research, industry reports, demographic analysis, and comparative studies of Starbucks' success in similar markets. Key factors including market dynamics, consumer behavior, competition, and strategic partnerships inform the analysis. Results: Bangladesh presents a promising market for Starbucks, with a growing coffee consumer base, favorable economic conditions, and low labor costs. Millennials and Gen Zs, a significant demographic, show a strong affinity for coffee, offering a sizable target audience. Lower operating costs enable investment in promotional activities and market research, while government initiatives to boost coffee production provide additional opportunities. Implications: Entering the Bangladeshi market requires Starbucks to tailor its business model to align with local preferences and market dynamics. Strategic considerations include investing in automated systems, understanding local culture, developing customized products and marketing strategies, and fostering strategic alliances with local partners. Originality: This case study provides a comprehensive analysis of Starbucks' potential expansion into Bangladesh, considering both market potential and strategic implications. By addressing the unique challenges and opportunities in the Bangladeshi market, the study offers insights into Starbucks' ability to adapt its business model and sustain growth in diverse global markets.